Œcumenicity in relation to the Church of England: four letters : with an appendix on the ultramontane and Gallican theories in relation to the œcumnicity and the Church of England / by Alexander Lord Lindsay - Crawford, Alexander William Crawford Lindsay (J. Murray, 1870)
I. On the catholicity of the Anglican Church.--II. On the claims of England versus Rome.--III. On the futility of attempts at reconciliation with the Church of Rome.--IV. On the (so-called) oecumenical council of 1869-70.